Association between tea consumption and stroke in the American adult females: analyses of NHANES 2011–2018 data - Miao, Yongyue; Ma, Sijia; Wu, Xian (Frontiers in Nutrition, 2024)
Background Epidemiological surveys show that there is a significant gender difference in the incidence of stroke, with females having a noticeably higher rate than males. Accordingly, it is crucial to seek preventive measures for stroke specifically targeted at females. Although previous studies have shown that tea has been proven to be negatively correlated with stroke, the relationship between tea and stroke in American adult females is still unclear. Therefore, we aimed to investigate the relationship between tea consumption and the occurrence of stroke in American adult females. Methods The data analyzed is derived from the NHANES database between 2011 and 2018. The quantity of tea consumed was gathered from a 24-h dietary review. Stroke was identified by using questionnaire. The association between tea consumption and stroke was investigated using a weighted regression model. Then we used interaction testing and subgroup analysis to conduct a thorough analysis. Simultaneously, the association between the sugar content in tea and stroke was examined. Results This study included 5731 adult females aged between 20 and 60 years. Compared to those who did not consume tea, the likelihood of stroke decreased by 9% for each additional 100 g of tea ingested by participants (OR = 0.91, 95%CI: 0.83–1.00). In the unadjusted model, those who drank 307.5–480 g of tea per day had a substantially decreased risk of stroke than those who did not drink tea (OR = 0.23, 95%CI: 0.08–0.64). After adjustment, this relationship also persisted (Model II: OR = 0.23, 95% CI: 0.08–0.64; Model III: OR = 0.23, 95% CI: 0.08–0.66). In both Model II and Model III, there was a statistically significant relationship between consuming 480–744 g of tea per day and the risk of stroke (Model II: OR = 0.39, 95%CI: 0.16–0.94; Model III: OR = 0.42, 95% CI: 0.18–0.98). Subgroup analysis revealed an interaction only with level of education (P = 0.031). Ultimately, we also demonstrated that people who drink sugar free tea have a lower risk of stroke, and even after adjusting for mixed factors. Conclusion This study suggested that proper tea consumption was associated with a lower risk of stroke in adult females, which recommended drinking sugar free tea.